Prevalence of peripheral neuropathy in patients with type II diabetes in a Family Health Unit in the City of Cascavel, State of Paraná (PR) (Research, Society and Development, 2025)
Introduction: Diabetic neuropathy is a common complication of diabetes mellitus (DM), characterized by damage to peripheral nerve fibers, resulting in sensory and motor alterations, as well as an increased risk of ulcerations and amputations. Objective: To determine the prevalence of peripheral neuropathy in patients diagnosed with DM for more than 5 years, followed at a Family Health Unit in Cascavel, Paraná, Brazil. Methodology: The Michigan Neuropathy Screening Instrument (MNSI-BRAZIL) was used, consisting of a questionnaire and physical examination, including tests for vibratory sensitivity, ankle reflexes, and monofilament assessment. Results: A total of 45 patients were evaluated, 64% of whom were female and all older than 50 years. Leg pain during walking (62.2%) and muscle cramps (62.2%) were the most prevalent symptoms. On physical examination, alterations in ankle reflexes, vibratory perception, and monofilament sensitivity were frequently observed. The prevalence of peripheral neuropathy was 20%, a value consistent with the literature. Conclusion: The study highlights the importance of early screening and appropriate management of diabetic neuropathy in primary care, aiming to reduce complications and improve patients’ quality of life.